Prolonging Payment Deadlines of Real Estate Tax Instalments to Entrepreneurs in Connection with Covid-19 in Poland: Basic Rules, Consequences of the Application of the Mechanism and Selected Disadvantages of Tax Resolutions - Popławski, Mariusz; Charkiewicz, Mariusz (Public Governance, Administration and Finances Law Review, 2021)
The primary aim of this article is to present fundamental principles resulting from Article 15q of the Covid Act – which contains the legal basis for passing tax resolutions – according to which the municipality councils may prolong to entrepreneurs payment deadlines of certain instalments in real estate tax. This paper discusses the consequences of introducing these preferences, as well as certain flaws of the tax resolutions adopted on the basis of the aforementioned regulation of the Act on Covid. The flaws were detected on the basis of the analysis of the resolutions adopted by regional accounting chambers finding shortcomings in the resolutions of municipality councils adopted on the basis of the aforementioned provision of the Act on Covid.